(untitled) (Kronika Bydgoska, 2012)
The Cosmetic Factory ‘Halina’ was one of the most interesting companies among chemical-pharmaceutical factories established in Bydgoszcz in the years 1920-1939. It was probably the biggest factory in this sector (even one hundred employees). The owners used an original and intense form of advertising. The company was established in 1927 by pharmacist Wacław Paździerski. Initially the factory was called the Chemical-Cosmetic Laboratory ‘Pharmachemia’. ‘Halina’ cream was the most famous series of products. At the end of 1938, the cream name was used for the company’s name. During the Second World War, the Paździerski family moved to Warsaw. Only their daughter Natalia - the right hand in the business of Wacław Paździerski - stayed in Bydgoszcz. She married Austrian Eugen Sartori, and therefore became a Citizen of the Third Reich. The married couple co-managed the business. They changed the company’s name to ‘Euwona’ Fabrik Kosmetischer und Pharmazeutischer Praparate. Meanwhile, Wacław Paździerski died in Warsaw. At the end of the war, Natalia and Eugen escaped to Austria. The heirs of Wacław Paździerski retumed from Warsaw to Bydgoszcz. The factory developed again. However, the Polish communist government nationalized and liąuidated the company in 1949/1950.